Study on Determination Method of Cyclic Siloxanes in Personal Care Products Collected from Hanoi, Vietnam - Tri, Tran Manh; Linh, Nguyen Le Hoai (VNU Journal of Science: Natural Sciences and Technology; Vol 34 No 2, 2018)
Cyclic siloxanes are widely used in beauty products as softener and polisher. Howeve, very few studies have reported the occurrence and amount of cyclic siloxanes in personal care products (PCPs). In this research, the analysis method of cyclic siloxanes including octamethylcyclotetrasiloxane (D4), decamethylcyclopentasiloxane (D5), and dodecamethylcyclohexasiloxane (D6) in PCPs was developed by using a gas chromatography-mass spectrometry (GC/MS) system. The method detection limits and the method quantification limits of individual cyclic siloxanes were 0.7 ng/g and 2.0 ng/g, respectively. Mean recoveries of surrogate compound (M4Q) and target compounds for the procedural blanks ranged from 88.5 to 94.9%. The recoveries of M4Q for real samples ranged from 75.5 to 120% (RSD: 6.8%). The optimal procedure was applied to measure the amount of D4, D5, and D6 in several samples of PCPs including shampoos, hair gels, and shower gels collected from retail stores in Hanoi, Vietnam. Mean concentrations of D4, D5 and D6 in PCPs ranged of 0.313 – 5.61 µg/g, 0.683 – 11.7 µg/g, and 0.294 – 3.38 µg/g, respectively.